PENGARUH CARA EKSTRAKSI TERHADAP SIFAT FISIKA DAN KIMIA SAGU - R Sudradjat (Pusat Penelitian dan Pengembangan Hasil Hutan, 1985)
The aim of this investigation is to evaluate the effect of extraction methodes on physical and chemical properties of sago. Extraction methodes comprise of fermentation, mechanical, and traditional.The result indicated that sago yield varies from 20,19% - 40,12%, acidity 0,89 - 0,98, moisture 13,39% -14,29%, ash 0,15% - 0,32%, protein 0,38% - 0,46%, crude fiber 0,27% - 0,31%, fat 0,17% - 0,23% and amylum 72,64% - 88,12%.Mechanical extractions gave the highest yield and amylum content. Fermentation methode show more acid than traditional. The traditional methode presents the highest ash content. This included that the mechanical methode seemed to be preferable for commercial application.